2014
DOI: 10.1016/j.jseaes.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The late Mesozoic–Cenozoic tectonic evolution of the South China Sea: A petrologic perspective

Abstract: Interpretations of seismic, gravity and magnetic anomalies and structural data on the coastal zone of southern part of Central Viet Nam (SCVN) and the adjacent Tertiary basins suggest several phases in the tectonic evolution of the study region since the Late Cretaceous to Quaternary. In this paper, we try to clarify the tectonic evolution of SCVN and the adjacent continental margin. The Cretaceous -Paleocene tectonic phase commenced after cessation of the West Pacific plutonic magmatic activity that produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
178
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(188 citation statements)
references
References 110 publications
9
178
0
1
Order By: Relevance
“…There are several basement high features around the SWSB, including the Macclesfield Bank, Reed Bank, Zhongjian Massif and Zhenghe Massif. Their Precambrian metamorphic basements (Yan and Liu 2004) suggested that they deformed little and remained as rigid blocks during the progressive continental lithosphere rifting, and have a continental origin from the South China Block (Yan et al 2014). They acted as a sharpener during the breakup of the continent until the advent of seafloor spreading of the SWSB (Ding and Li 2016).…”
Section: Geological Settingmentioning
confidence: 99%
“…There are several basement high features around the SWSB, including the Macclesfield Bank, Reed Bank, Zhongjian Massif and Zhenghe Massif. Their Precambrian metamorphic basements (Yan and Liu 2004) suggested that they deformed little and remained as rigid blocks during the progressive continental lithosphere rifting, and have a continental origin from the South China Block (Yan et al 2014). They acted as a sharpener during the breakup of the continent until the advent of seafloor spreading of the SWSB (Ding and Li 2016).…”
Section: Geological Settingmentioning
confidence: 99%
“…The pyroxenites-andesitesbasanites trend of the rocks of the Valovayam River is also significantly displaced toward the enriched EM-II component, where mantle metasomatism is best expressed. The displacement of some data points toward an increasing radiogenic lead component Δ208/204 and Δ207/204 toward the EM-II component may indicate the contribution of the asthenospheric mantle reservoir [38] to the formation of this type of xenoliths. The localities of the "within-plate" xenoliths are confined to the large Sr-isotope anomalies of Central Kamchatka (Bakening volcano) and the Bering Sea region (Valovayam River and Cape Navarin), thus reflecting traces of penetration of asthenospheric diapirs into the lower lithosphere [11].…”
Section: Discussionmentioning
confidence: 98%
“…Those models, however, are in contradiction with a few observations including the amount and the precise age of motion of Red River fault, as well as the kinematic evolution of the SCS spreading (Searle, 2006). Those models completely overlooked the possible presence of a deep mantle upwelling whose initiation likely coincided with the SCS opening (Yan et al, 2014).…”
Section: Implication To Tectonic Evolution Of the South China Sea (Scs)mentioning
confidence: 88%
“…However, with a history of extensive riftings and possible presences of deep mantle upwelling (Wang et al, 2013) as well as a late Mesozoic subduction zone (Yan et al, 2014), the mantle structure beneath Leiqiong is of course a complex 3-D structure. As shown in Fig.…”
Section: -D Velocity Variation Verses 1-d Modelmentioning
confidence: 99%